Special features of the surface layer structure of ferritic-martensitic EP-823-Sh steel after prolonged exposure to the flowing lead at 630 °C under low oxygen concentration - Polekhina, Nadezhda A.; Litovchenko, Igor Yu; Almaeva, Kseniya V.; Akkuzin, Sergey A.; Linnik, Valeria V.; Moskvichev, Evgeny N.; Chernov, Vyacheslav M.; Naumenko, I. A.; Saifutdinova, M. S.; Leontyeva-Smirnova, M. V. (Journal of nuclear materials)
The microstructure, the phase and elemental compositions of the surface and near-surface layers of the EP-823-Sh reactor 12 % chromium ferritic-martensitic steel after holding in an oxygen-containing (C[o] = (4–8) × 10−7 wt. %) molten lead flow at 630 °C for 2500 h are investigated. As a result of the liquid lead interaction with the steel samples, an oxide film from 250 nm to 18 μm is formed on their surfaces. It is a layer of Fe-Cr spinel enriched in Si and Mn. An internal oxidation zone of steel with a thickness of 4–10 μm is found under the scale layer. In the internal oxidation zone, both inside the matrix grains and along their boundaries, oxide particles (Cr, Si, Mn)2 O3 and Fe3 O4 with sizes up to 50 nm are observed. Below this zone, a matrix layer depleted in chromium (with a thickness of ≤ 15 μm) is located. The features of the oxidation zone structure are discussed, the role of alloying elements is determined (identified and validated), and a possible mechanism for the formation of such a zone is proposed.